2017
DOI: 10.1093/dnares/dsx003
|View full text |Cite
|
Sign up to set email alerts
|

Integrated miRNA and mRNA expression profiling reveals the response regulators of a susceptible tomato cultivar to early blight disease

Abstract: Early blight, caused by the fungus Alternaria solani, is a devastating foliar disease of tomatoes, causes massive yield loss each year worldwide. Molecular basis of the compatible host–pathogen interaction was elusive. We adopted next generation sequencing approach to decipher miRNAs and mRNAs that are differentially expressed during Alternaria-stress in tomato. Some of the interesting findings were also validated by alternative techniques. Our analysis revealed 181 known-miRNAs, belonging to 121 miRNA familie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 34 publications
(53 reference statements)
3
31
1
Order By: Relevance
“…Tomato genome encodes about 30 miRNAs which are potentially derived from at least two alternative genes. 27 Among these, MIR167 precursors are likely expressed from five different genes. Previous literature 13 and our experimental evidences (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Tomato genome encodes about 30 miRNAs which are potentially derived from at least two alternative genes. 27 Among these, MIR167 precursors are likely expressed from five different genes. Previous literature 13 and our experimental evidences (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, an extensive interaction analysis of mRNA and miRNA uncovered the molecular interactions between pathogen Potato virus Y and tobacco (Guo et al, 2017). Similarly, another study identified important regulators of Alternaria-stress response in tomato (Sarkar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs control the expression of genes in spatial and temporal-specific manner in response to stress. A number of studies have suggested the importance of miRNAs in plant defense response (Kohli et al, 2014;Sarkar et al, 2017). Although miRNAs have been extensively studied in plants, their regulatory mechanism is still unclear on miRNA-mediated response to biotic stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…miRNAs are a class of small endogenous noncoding RNAs of about 18 to 25 nucleotides (nts), which are known to play diverse gene regulatory functions at the posttranscriptional level . They function by preferentially binding to the 3′‐untranslated region (3′‐UTR) of target mRNAs through their seed region (2‐7/8 nts) causing either degradation or translational inhibition of the corresponding target mRNAs .…”
Section: Introductionmentioning
confidence: 99%